1987
DOI: 10.1111/j.1600-0714.1987.tb00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mucosal reaction related to Candida albicans isolates

Abstract: Allen CM, Beck FM. Differences in mueosal reaetion related to Candida albicans isolates. , 1 Oral Pathol 1987; 16: 89-93. In order to examine the behavior of Candida albicans in an oral mueosal model, 16 isolates of the organism were coUeeted from a variety of elinieal settings and were inoculated weekly, in equal numbers and eoncentrations, into the mouths of separate groups of 20 female Sprague-Dawley rats. Oral swabs were taken bi-weekly in order to monitor the presenee of the yeast. After 16 weeks, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

1990
1990
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
1
15
0
2
Order By: Relevance
“…The palatal smears from the experimental infection yielded yeasts that were almost exclusively in the hyphal form, as in Candida-associated denture stomatitis (30,34). Also, a number of studies by others with the SpragueDawley rat model of oral candidiasis have detected colonization patterns and lesions that were similar to human lesions both microscopically and histologically (4,5). Earlier studies by Russell and Jones (156) and Jones et al (82) using a rat model also demonstrated that Candida carriage and infectivity in this animal are similar to those in humans.…”
Section: Need For and Clinical Relevance Of Animal Modelsmentioning
confidence: 93%
See 1 more Smart Citation
“…The palatal smears from the experimental infection yielded yeasts that were almost exclusively in the hyphal form, as in Candida-associated denture stomatitis (30,34). Also, a number of studies by others with the SpragueDawley rat model of oral candidiasis have detected colonization patterns and lesions that were similar to human lesions both microscopically and histologically (4,5). Earlier studies by Russell and Jones (156) and Jones et al (82) using a rat model also demonstrated that Candida carriage and infectivity in this animal are similar to those in humans.…”
Section: Need For and Clinical Relevance Of Animal Modelsmentioning
confidence: 93%
“…The same workers noted the distinct strain-related patterns of C. albicans infections on the dorsal lingual mucosa of immunocompetent rats (3,4). They showed that while some isolates produced lesions particularly on the posterior-dorsal lingual mucosa accompanied by flattening of the normal papillary architecture of the epithelium, another group failed to produce any mucosal lesions.…”
Section: Sprague-dawley Rat Modelmentioning
confidence: 95%
“…Candidosis of the dorsal rat tongue has been reported by Allen et al (1983Allen et al ( , 1987Allen et al ( , 1989), Russel (1974, 1975) as a characteristic, clinically apparent, lesion in the gigant conical papillae region. This clinical lesion was observed in 70 %, and infection with Candida spp.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the clinical presentation of the disease could be influenced by any one of the several factors, such as host immune status, diet, salivary flow rate and salivary composition, endocrine disturbances, use of antibiotics or steroids, and the presence of dentures (Allen and Beck 1987). These factors are eliminated in experiment and also our animal model is a suitable tool for detection of pathogenicity of yeast microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation